Credit supply and demand in unconventional times - Carlo Altavilla; Miguel Boucinha; Sarah Holton; Steven Ongena (European Central Bank (ECB), 2018)
Do borrowers demand less credit from banks with weak balance sheet positions? To answer this question we use novel bank-specific survey data matched with confidential balance sheet information on a large set of euro area banks. We find that, following a conventional monetary policy shock, bank balance sheet strength influences not only credit supply but also credit demand. The resilience of lenders plays an important role for firms when selecting whom to borrow from. We also assess the impact on credit origination of unconventional monetary policies using survey responses on the exposure of individual banks to quantitative easing and negative interest rate policies. We find that both policies do stimulate loan supply even after fully controlling for bank-specific demand, borrower quality, and balance sheet strength.
Keywords: E51; G21; 330; credit demand and supply; bank lending survey; balance sheet strength; nonstandard monetary policy